(untitled) (Journal of Politica Governo, 2026)
The phenomenon of post-truth politics has shifted the epistemic foundations of electoral democracy by placing emotions and identity above empirical facts. In the context of elections, digital disinformation not only influences individual political preferences but also erodes the legitimacy of democratic institutions and public trust in electoral outcomes. This article aims to analyze the mechanisms of disinformation, cross-national patterns, its impact on the quality of democracy, and policy responses during the 2021–2025 period. The study employs a Systematic Literature Review approach of 18 reputable international journal articles. The findings indicate that disinformation operates through a reinforcement effect, polarizing perceptions of electoral integrity, and is further exacerbated by the emergence of AI-generated content and deepfakes that create an epistemic crisis. Comparative analysis of the United States, Brazil, Indonesia, and the European Union reveals patterns of delegitimization, identity polarization, and manipulation of strategic issues such as migration and religion. Mitigation efforts include digital literacy initiatives, algorithmic transparency, and the strengthening of journalism, although their effectiveness is constrained by partisan polarization. This article argues that disinformation in the post-truth era constitutes a systemic threat to electoral democracy and requires a multidimensional and sustainable response.